CONSUMER EDUCATION, FAMILY AND REFERENCE GROUP INFLUENCE IN ASO EBI SELECTION IN SOUTHWEST NIGERIA - Olugbamigbe, Abigail Olukemi (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
In Nigeria, the selection of aso ebi, a traditional attire worn for special occasions, is influenced by various social and familial factors. This study examined the relationship between family influence, reference group influence, and consumer education in the selection of aso ebi in Southwest Nigeria. Two research questions were posed, and two hypotheses were tested at a 0.05 level of significance. A correlational design was employed to collect data from 1200 adult individuals (aged 18 years and above) in the Southwestern geopolitical zone of Nigeria, covering Ekiti, Lagos, Ogun, Ondo, Osun, and Oyo states. A validated, reliable, self-structured questionnaire titled